Co-circulation of Chikungunya and Dengue viruses in Dengue endemic region of New Delhi, India during 2016. Issue 13 (10th July 2018) - Hisamuddin, M.; Tazeen, A.; Abdullah, M.; Islamuddin, M.; Parveen, N.; Islam, A.; Faizan, M. I.; Hamza, A.; Naqvi, I. H.; Verma, H. N.; Malik, A.; Ahmed, A.; et al.
Abstract: Co-circulation of Chikungunya and Dengue viral infections (CHIKV and DENV) have been reported mainly due to transmission by common Aedes vector. The purpose of the study was to identify and characterise the circulating strains of CHIKV and DENV in DENV endemic region of New Delhi during 2016. CHIKV and DENV were identified in the blood samples ( n = 130) collected from suspected patients by RT-PCR. CHIKV was identified in 26 of 65 samples (40%). Similarly, DENV was detected in 48 of 120 samples (40%). Co-infection with both the viruses was identified in five (9%) of the samples. Interestingly, concurrent infection with DENV, CHIKV and Plasmodium vivax was detected in two samples. CHIKV strains ( n = 11) belonged to the ECSA genotype whereas DENV-3 sequences ( n = eight) clustered in Genotype III by phylogenetic analysis. Selection pressure of E1 protein of CHIKV and CprM protein of DENV-3 revealed purifying selection with four and two positive sites, respectively. Four amino acids of the CHIKV were positively selected and had high entropy suggesting probable variations. Co-circulation of both viruses in DENV endemic regions warrants effective monitoring of these emerging pathogens via comprehensive surveillance for implementation of effective control measures.